International Journal of Practices in Teaching and Learning Vol 1 No1 / Dr Rofiza Aboo Bakar ... [et al.] - Aboo Bakar, Dr Rofiza; Adnan, Dr Nur Ilianis; Alias, Dr Salina; Hassan, Norhaslinda (2021)
Welcome to the inaugural issue of the International Journal of Practices in Teaching and Learning (IJPTL): a peer-reviewed journal in the field of teaching and learning and is launched by STALITE (Society for Teaching and Learning for Tertiary Education). IJPTL is only making its small and humble beginning. However, it aims to provide a cross-disciplinary medium for educators to publish innovative practices in teaching and learning that can be shared for the benefit of all. This journal whose research articles are written in an easy-read manner, seeks to aspire both new and experienced writers to share their expertise and perspectives in fields that they are involved in. The theme for this inaugural issue is Corporate Social Responsibility (CSR). Although IJPTL is new and has not made its mark as an indexed journal, its research articles have gone through a double-blind peer-review process. This is done since it hopes to savour benefits, such as original and high standard research papers, and significant contributions. I hope readers can attain meaningful ideas put forth in this issue, and I look forward to many more varied discussions in subsequent issues. Finally, I would like to take this opportunity to thank the associate editors, editorial board members, international peer reviewers, contributing writers, and many others for making IJPTL and this first issue possible. Special thanks also go to the members of the STALITE publishing team, and most importantly, Professor Ts. Dr. Salmiah Kasolang, who sparked the wonderful idea of IJPTL that she terms as an "affectionate' journal which inspires new writers cum researchers to write and publish with no fear of rejection. We make the best 'Thinker - Connector - Doer Team' and we hope to "do ordinary things with extraordinary love", always.